The Implementation of Character Education in Physics Subjects through Salingtemas Approach - Reski Idamayanti; Irma Sakti (Jurnal Pendidikan Fisika, 2020)
Character education is a process of instilling certain character values which at the same time students are able to grow their distinctive character when running life into old age. In physics subjects are able to make a meaningful contribution to character education. The application of character education in learning needs to be adjusted to the approach used. One of them is by applying Salingtemas approach in learning. The research location was SMP Negeri 1 Palakka, bone district with a total sample of 30 students. This research uses a descriptive qualitative approach. Data analysis techniques used in this study are descriptive analysis techniques, data obtained from interviews, observations, documentation, followed by describing (describing), analyzing and interpreting in depth especially data relating to character formation and character description of students. Broadly speaking, the stages used to analyze data include data reduction, data display, conclusions and verification. Character valuesformed by applying character edification with a mutual approach are disciplined, religious, honest, logical thinking, creative, independent, creative, communicative, cooperation, mutual respect, self-confidence, polite, honest, responsible, hard work, caring for the environment and Social care.Keywords: Character Education, The Salingtemas ApproachPendidikan karakter adalah merupakan proses menanamkan nilai karakter tertentu yang sekaligus peserta didik mampu menumbuhkan karakter khasnya pada saat menjalankan kehidupan hingga tua. Pada mata Pelajaran fisika mampu memberikan kontribusi berarti terhadap pendidikan karakter. Penerapan pendidikan karakter dalam pembelajaran perlu disesuaikan dengan pendekatan yang digunakan. Salah satunya dengan menerapkan pendekatas Salingtemas dalam pembelajaran. Lokasi penelitian di SMP Negeri 1 palakka kabupaten bone dengan jumlah sampel sebanyak 30 peserta didik. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis deskriptif, data yang diperoleh dari hasil wawancara, observasi, dokumentasi, dilanjutkan dengan mendeskripsikan (memaparkan), menganalisis dan menginterpretasi secara mendalam terutama data yang berhubungan dengan  pembentukan karakter dan gambaran karakter peserta didik. Secara garis besar tahap-tahap yang digunakan untuk menganalisis data diantaranya reduksi data, display data, kesimpulan dan verifikasi.  Nilai Karakter yang terbentuk menerapkan pendidikan karakter dengan pendekatan salingtemas adalah disiplin, religius, jujur, berpikir logis, kreatif, mandiri, kreatif, komunikatif, kerja sama, saling menghargai, percaya diri, santun, jujur, bertanggung jawab, kerja keras, peduli lingkungan dan peduli sosial.Kata kunci: Pendidikan Karakter, Pendekatan Salingtemas